Phospholipase D1 regulates lymphocyte adhesion via upregulation of Rap1 at the plasma membrane. - Mor, A; Wynne, J; Ahearn, I; Dustin, M; Du, G; Philips, MR (2009)
Rap1 is a small GTPase that modulates adhesion of T cells by regulating inside-out signaling through LFA-1. The bulk of Rap1 is expressed in a GDP-bound state on intracellular vesicles. Exocytosis of these vesicles delivers Rap1 to the plasma membrane, where it becomes activated. We report here that phospholipase D1 (PLD1) is expressed on the same vesicular compartment in T cells as Rap1 and is translocated to the plasma membrane along with Rap1. Moreover, PLD activity is required for both translocation and activation of Rap1. Increased T-cell adhesion in response to stimulation of the antigen receptor depended on PLD1. C3G, a Rap1 guanine nucleotide exchange factor located in the cytosol of resting cells, translocated to the plasma membranes of stimulated T cells. Our data support a model whereby PLD1 regulates Rap1 activity by controlling exocytosis of a stored, vesicular pool of Rap1 that can be activated by C3G upon delivery to the plasma membrane.